Problem-Focused Coping in Student Academic Stress - Putranto, Alridho Raihan Airlangga; Damayanti, Yeni; Takalapeta, Theodora (Journal of Health and Behavioral Science, 2025)
Academic stress is one of the problems faced by Psychology students of the Faculty of Public Health, Nusa Cendana University, especially when facing various academic demands. This study aims to examine the effect of problem-focused coping, a coping strategy centered on problem-solving, on academic stress. The research employed a quantitative explanatory approach with a survey design. Data were collected through questionnaires from 180 students. The analysis revealed that increased use of problem-focused coping was significantly negatively correlated with academic stress (p = 0.001). These findings underscore the importance of implementing problem-focused coping strategies to reduce academic stress and support the improvement of students’ well-being.